Energetic Particle Data From the Global Positioning System Constellation. Issue 2 (15th February 2017) - Morley, S. K.; Sullivan, J. P.; Carver, M. R.; Kippen, R. M.; Friedel, R. H. W.; Reeves, G. D.; Henderson, M. G.
Abstract: Since 2000, Los Alamos National Laboratory (LANL) Combined X‐ray and Dosimeter (CXD) and Burst Detector Dosimeter for Block II‐R (BDD‐IIR) instruments have been fielded on Global Positioning System (GPS) satellites. Today, 21 of the 31 operational GPS satellites are equipped with a CXD detector and a further 2 carry a BDD‐IIR. Each of these instruments measures a wide range of energetic electrons and protons. These data have now been publicly released under the terms of the Executive Order for Coordinating Efforts to Prepare the Nation for Space Weather Events. The specific goal of releasing space weather data from the GPS satellites is to enable broad scientific community engagement in enhancing space weather model validation and improvements in space weather forecasting and situational awareness. The time period covered by this data release is approximately 16 years, which corresponds to more than 167 satellite years of data. The large number of GPS satellites, distributed over six orbital planes, will provide important context for ongoing and historical science missions, as well as enabling new types of research not previously possible.